Functional and antioxidant properties of angelwing clam (Pholas Orientalis) hydrolysate produced using alcalase / Normah Ismail, Juliana Mahmod and Awatif Khairul Fatihin Mustafa Kamal - Ismail, Normah; Mahmod, Juliana; Mustafa Kamal, Awatif Khairul Fatihin (Research Management Institute (RMI), 2014)
In this study, Hydrolysate from angelwing clam (Pholas orientalis) was produced at 0, 1, 2 and 3 hrs and E/S ratio of 0.5 and 3% using alcalase where the pH and temperature were kept constant at pH 8.5 and 60°C, respectively. The hydrolysates were analysed for antioxidant and functional properties such as solubility, emulsifying properties and water and oil holding capacity. Degree of hydrolysis (DH), yield, functional and antioxidant properties were influenced by the hydrolysis time and E/S ratio. Higher enzyme concentration (E/S 3%) and longer hydrolysis time increased the DH. Yield was higher at E/S 3% but reduced with hydrolysis time. Longer hydrolysis time produced more soluble hydrolysate and higher metal chelating activity but lower in emulsifying properties and DPPH activity. Higher enzyme concentration resulted in increase only in solubility and metal chelating activity. This study revealed that enzymatic hydrolysis using alcalase should be performed at shorter hydrolysis time using intermediate concentration of enzyme (E/S between 0.5 to 3%) in order to produce angelwing clam hydrolysate with collectively good functional and antioxidant properties.